Bio-based conductive adhesive as well as preparation method and application thereof

By compounding bio-based adhesives with tackifiers, conductive fillers, and crosslinking agents, a bio-based conductive adhesive with low environmental impact and excellent conductivity and adhesion properties was prepared, solving the problems of environmental impact and insufficient performance of petroleum-based conductive adhesives in the prior art.

CN119264833APending Publication Date: 2025-01-07HANPIN (KUNSHAN) ELECTRONIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411391043.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing conductive adhesives rely on petroleum-based polymers, resulting in significant environmental impact. Their conductivity and adhesion properties need improvement, and their preparation processes are complex.

Method used

Bio-based conductive adhesives are prepared by compounding bio-based adhesives with tackifiers, conductive fillers and crosslinking agents, and then using a drying process. The crosslinking agent enriches on the surface to increase reactive groups and form stable and continuous contacts.

Benefits of technology

A bio-based conductive adhesive with low environmental impact and excellent conductivity and adhesion properties was prepared, with an average resistance of less than 0.07Ω and a peel strength of more than 800gf, which meets the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264833A_ABST
    Figure CN119264833A_ABST
Patent Text Reader

Abstract

The invention provides a bio-based conductive adhesive as well as a preparation method and application thereof. The bio-based conductive adhesive is prepared from the following raw materials in parts by weight: 100 parts of a bio-based adhesive, 1-80 parts of a tackifier, 3-30 parts of conductive filler and 0.01-5 parts of a cross-linking agent. The main raw materials of the bio-based conductive adhesive provided by the invention come from bio-based materials, so that the influence on the environment can be reduced, and the bio-based conductive adhesive is good in conductivity and adhesive property and simple in preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive adhesives, and in particular relates to a bio-based conductive adhesive and a preparation method and application thereof. Background Art

[0002] Conductive tape is widely used in electronic 3C products, playing the role of electromagnetic shielding, static electricity conduction (static discharge), circuit bonding and gap sealing. For example: there are many circuits on traditional circuit boards, and some places on the circuit boards are not suitable for welding, so conductive tape is needed for connection and bonding; some electronic components require electromagnetic shielding to eliminate electrical signal interference, and conductive tape is needed for physical shielding; some precision components will be interfered by static electricity, and good conductive tape can be used for static discharge, so conductive adhesives and conductive tapes came into being.

[0003] CN111500215A discloses a pressure-sensitive conductive adhesive, which comprises the following components by weight: 80-90 parts of acrylic resin slurry and 30-50 parts of conductive filler, wherein the conductive filler comprises 50-60% of graphene-coated copper powder by weight, and the rest is one or more of conductive silver powder, aluminum silver-plated powder, nano zinc oxide, and nano aluminum oxide; the acrylic resin slurry comprises the following components by weight: 10-20 parts of acrylic hard monomer, 20-30 parts of acrylic soft monomer, 1-5 parts of functional monomer, 0.1-0.5 parts of initiator, 0.5-1 parts of coupling agent, 0.5-2 parts of cross-linking agent, and 120-150 parts of ethyl acetate; the pressure-sensitive conductive adhesive provided by the technical solution has high initial adhesion and high lasting adhesion, as well as good conductive performance and low raw material cost, but the conductive performance of the conductive adhesive provided by the invention is poor.

[0004] CN116836661A discloses an epoxy resin-based conductive adhesive and a preparation method thereof. The specific steps of preparing the epoxy resin-based conductive adhesive are as follows: (1) preparing a 3,4-dioxyethylenethiophene / 5-cyanoindole copolymer film by an electrochemical method; (2) dissolving the copolymer film in dimethyl sulfoxide to obtain a solution a; dissolving sulfate in deionized water, adding hydroxylated nano titanium diboride powder and carboxylated nano titanium diboride powder and dispersing them uniformly to obtain a dispersion liquid b; adding the dispersion liquid b to the solution a, stirring magnetically and dispersing ultrasonically for 20 to 40 minutes; the sulfate is at least one of copper sulfate and zinc sulfate; the copolymer film, sulfate, hydroxylated nano titanium diboride powder, carboxylated nano titanium diboride powder, dimethyl sulfoxide, and deionized water are mixed together. The mass ratio is 10: (1-2): 15: 15: (55-60): (40-45); (3) first heat to 80-90°C and keep for 6-8h, then cool to 45-50°C and keep for 55-60h, cool naturally, and freeze-dry to remove moisture and dimethyl sulfoxide to obtain a double network composite aerogel; (4) grind the composite aerogel into powder, mix it evenly with epoxy resin matrix, curing agent, plasticizer, and acetone to obtain a conductive adhesive; the mass ratio of composite aerogel powder, epoxy resin matrix, curing agent, plasticizer, and acetone is (60-70): (30-40): (2-3): (2-4): (10-12). This technical solution prepares an epoxy resin adhesive with good conductive and bonding properties, but the preparation process is relatively complicated.

[0005] As the world pays more and more attention to the environment and under the background of carbon neutrality and carbon peak, various industries have increasing demand for environmentally friendly and sustainable materials. Traditional conductive adhesives can be divided into two categories based on their main components. The first category is the epoxy resin conductive system, and the second category is the acrylic resin conductive system. Both are based on petroleum-based polymers, mainly rely on fossil resources such as petroleum, and may face stricter supervision.

[0006] Therefore, it is necessary to develop a bio-based conductive adhesive with low dependence on fossil resources such as petroleum, good conductivity and bonding properties, and simple preparation process. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a bio-based conductive adhesive and its preparation method and application. The main raw material of the bio-based conductive adhesive comes from bio-based materials, which can reduce the impact on the environment, and has good conductivity and bonding properties and a simple preparation process.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a bio-based conductive adhesive, comprising the following components in parts by weight: 100 parts of a bio-based adhesive, 1 to 80 parts of a tackifier (e.g., 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, or 70 parts, etc.), 3 to 30 parts of a conductive filler (e.g., 5 parts, 10 parts, 15 parts, 20 parts, or 25 parts, etc.), and 0.01 to 5 parts of a cross-linking agent (e.g., 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, or 4.5 parts, etc.).

[0010] In the present invention, the bio-based adhesive is derived from biomass and does not rely on fossil resources such as petroleum. It can reduce the impact on the environment to a certain extent and meet the requirements of sustainable development. The bio-based conductive adhesive prepared by compounding it with a tackifier, a conductive filler and a cross-linking agent has the characteristics of good conductivity and bonding performance. The cross-linking agent can react with the polymers in the bio-based adhesive and the tackifier and cross-link to form a macromolecular chain, thereby increasing the overall cross-linking density of the conductive adhesive, and can also be enriched on the surface of the bio-based conductive adhesive, increasing the number of reactive groups on the surface of the bio-based conductive adhesive, and increasing the bonding performance.

[0011] Preferably, the bio-based adhesive comprises a bio-based acrylic adhesive.

[0012] Preferably, the tackifier comprises a bio-based tackifying resin.

[0013] In the present invention, the bio-based tackifying resin is derived from biomass and does not rely on fossil resources such as petroleum, which can reduce the impact on the environment to a certain extent.

[0014] Preferably, the bio-based tackifying resin comprises any one of rosin resin, modified rosin resin, petroleum resin, terpene resin, terpene phenolic resin or phenolic resin, or a combination of at least two thereof.

[0015] Preferably, the weight proportion of the tackifier in the raw materials for preparing the bio-based conductive adhesive is 1 to 40 parts (eg, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or 35 parts, etc.).

[0016] Preferably, the softening point of the tackifier is -40 to 150°C, for example, -20°C, -10°C, 0°C, 20°C, 40°C, 60°C, 80°C, 100°C, 120°C or 140°C, and more preferably 0 to 120°C.

[0017] Preferably, the conductive filler comprises metallic conductive particles.

[0018] Preferably, the metal conductive particles include any one of gold powder, copper powder, silver powder, nickel powder, aluminum powder, nickel powder or nickel-coated graphite, or a combination of at least two thereof, and more preferably nickel powder.

[0019] In the present invention, the gold powder has an excellent conductive effect but a high cost; the copper powder has an excellent conductive effect but copper will increase its resistance due to the influence of ambient temperature, and it is extremely difficult to ensure the resistance stability when used in chemical liquids; the silver powder has an excellent conductive effect but its market share is not high and its cost is relatively high; the aluminum powder has poor conductivity; the nickel powder has an excellent conductive effect, good solvent resistance and controllable cost.

[0020] Preferably, the weight proportion of the conductive filler in the raw material for preparing the bio-based conductive adhesive is 5 to 15 parts (for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts, etc.).

[0021] Preferably, the nickel powder includes any one of branched chain nickel powder, flaky nickel powder, spherical nickel powder, porous microspherical nickel powder or long chain nickel powder, or a combination of at least two thereof, and branched chain nickel powder is more preferred.

[0022] Preferably, the D of the branched nickel powder is 50 The particle size is 5 to 40 μm (eg, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or 35 μm, etc.), and more preferably 10 to 30 μm.

[0023] Preferably, the crosslinking agent comprises isocyanate silane and / or epoxy silane, more preferably isocyanate silane and epoxy silane.

[0024] Preferably, the weight proportion of the crosslinking agent in the raw material for preparing the bio-based conductive adhesive is 0.01 to 1 part (for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part, etc.).

[0025] In a second aspect, the present invention provides a method for preparing the bio-based conductive adhesive as described in the first aspect, the preparation method comprising mixing a bio-based adhesive, a tackifier, a conductive filler, a cross-linking agent and a solvent, and drying to obtain the bio-based conductive adhesive.

[0026] In the present invention, the preparation method of the bio-based conductive adhesive is subjected to a drying process to remove the solvent. In the process, the cross-linking agents isocyanate silane and epoxy silane are gradually enriched on the surface under the action of surface tension. The enrichment of the cross-linking agent can increase the number of reactive groups on the surface of the bio-based conductive adhesive and improve the bonding performance. The volume shrinkage caused by the volatilization of the solvent and the curing of the components allows the conductive fillers to form stable and continuous contact with each other, so that the bio-based conductive adhesive has conductivity.

[0027] Preferably, the solvent comprises ethyl acetate.

[0028] Preferably, the drying temperature is 80-160°C, for example, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0029] Preferably, the drying speed is 3 to 10 m / min, for example, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min, etc.

[0030] Preferably, the drying step further includes a aging step.

[0031] Preferably, the aging temperature is 20-30°C (for example, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C or 29°C, etc.), and the time is 3-7 days (for example, 4 days, 5 days or 6 days, etc.).

[0032] In a third aspect, the present invention provides a bio-based conductive tape, wherein the bio-based conductive tape includes a tape without a substrate or a tape containing a substrate;

[0033] The substrate-free adhesive tape comprises a first release film layer, an adhesive layer and a second release film layer stacked in sequence, wherein the adhesive layer is made of the bio-based conductive adhesive as described in the first aspect;

[0034] The substrate-containing adhesive tape includes a single-sided adhesive tape or a double-sided adhesive tape;

[0035] The single-sided tape is composed of a release film layer, an adhesive layer and a conductive substrate layer stacked in sequence, and the adhesive layer is made of the bio-based conductive adhesive as described in the first aspect;

[0036] The double-sided tape is composed of a first release film layer, a first adhesive layer, a conductive substrate layer, a second adhesive layer and a second release film layer stacked in sequence, and the first adhesive layer and the second adhesive layer are each independently made of the bio-based conductive adhesive described in the first aspect.

[0037] Preferably, the adhesive layer in the substrate-free tape, the adhesive layer in the single-sided tape, the first adhesive layer and the second adhesive layer in the double-sided tape are each independently 0.01 to 0.05 mm, for example, 0.015 mm, 0.02 mm, 0.025 mm, 0.03 mm, 0.035 mm, 0.04 mm or 0.045 mm.

[0038] Preferably, the first release film layer in the substrate-free tape, the second release film layer in the substrate-free tape, the release film layer in the single-sided tape, the first release film layer in the double-sided tape and the second release film layer in the double-sided tape each independently comprise a plain release film.

[0039] Preferably, the thickness of the plain release film is 0.025-0.15 mm, for example, 0.04 mm, 0.06 mm, 0.08 mm, 0.10 mm, 0.12 mm or 0.14 mm.

[0040] Preferably, the conductive substrate layers in the single-sided tape and the double-sided tape each independently include any one of copper foil, aluminum foil or conductive cloth, more preferably copper foil.

[0041] Preferably, the copper foil is electrolytic copper foil.

[0042] Preferably, the copper foil has a thickness of 0.002 to 3.0 mm (eg, 0.004 mm, 0.01 mm, 0.05 mm, 0.1 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm or 2.5 mm, etc.), more preferably 0.006 to 0.2 mm, and even more preferably 0.018 mm.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The bio-based adhesive of the present invention is derived from biomass, does not rely on fossil resources such as petroleum, and can reduce the impact on the environment. The bio-based conductive adhesive prepared by compounding it with a tackifier, a conductive filler and a cross-linking agent has the characteristics of good conductivity and bonding performance, simple preparation process and green environmental protection. The bio-based material content of the bio-based adhesive is ≥60wt%, and the 1-inch bio-based conductive tape made of the bio-based adhesive is 2 The average resistance is less than 0.07Ω, the peel force is greater than 800gf, preferably 1inch 2 The average resistance is less than 0.03Ω, and the peeling force at room temperature is greater than 1600gf. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 A schematic diagram of the structure of the bio-based conductive tape provided in Example 1;

[0046] Among them, 1-conductive substrate layer; 2-adhesive layer; 3-release film layer. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] The sources of some raw materials in the following examples and comparative examples are as follows:

[0049] Bio-based adhesive: Bio-based acrylic adhesive, brand name SP002794, with 80% bio-based content, manufactured by Toyo Ink of Japan;

[0050] Acrylic pressure-sensitive adhesive: brand name XPHGS04, manufacturer is Kunshan Shimei New Material Technology Co., Ltd., solid content is about 48%;

[0051] Rosin resin: brand name SYLVALITE TM 2200, with a bio-based content of 85%, a softening point of 98°C, and is manufactured by Kraton, USA;

[0052] Terpene resin: brand name SYLVARES TM 3115, with a bio-based content of 85%, a softening point of 115°C, and is manufactured by Kraton, USA;

[0053] Isocyanate silane: brand name XPHJ-G01C, manufacturer: Changxing Materials Industry Co., Ltd.;

[0054] Epoxy silane: The brand name is XPHJ-G02C, and the manufacturer is Changxing Materials Industry Co., Ltd.

[0055] Example 1

[0056] This embodiment provides a bio-based conductive tape and a preparation method thereof. The bio-based conductive tape is a single-sided tape, such as Figure 1 As shown, the single-sided tape is composed of a conductive substrate layer 1, an adhesive layer 2 and a release film layer 3 which are stacked in sequence;

[0057] The conductive substrate layer 1 is an electrolytic copper foil with a thickness of 0.018 mm;

[0058] The adhesive layer 2 is made of a bio-based conductive adhesive and has a thickness of 0.020 mm;

[0059] The release film layer 3 is a PET plain release film with a thickness of 0.05 mm.

[0060] The preparation method of the single-sided adhesive tape comprises the following steps:

[0061] 100 parts by weight of bio-based adhesive (bio-based acrylic adhesive, SP002794), 5 parts by weight of tackifier (rosin resin), 5 parts by weight of conductive filler (branched nickel powder, D 50 The particle size is 10 μm), 1.2 parts by weight of isocyanate silane (XPHJ-G01C), 0.01 parts by weight of epoxy silane (XPHJ-G02C) and 80 parts by weight of ethyl acetate are mixed to form a glue solution, which is coated on one side of the release film layer and dried in an oven at 120°C. The inlet and outlet air volume of the oven is 4500m 3 / h, the drying speed is 8m / min to form an adhesive layer, which is laminated with the conductive substrate layer and placed at room temperature (25°C) for 5 days for aging to obtain the single-sided tape.

[0062] Example 2

[0063] This embodiment provides a bio-based conductive tape and a preparation method thereof, wherein the bio-based conductive tape is a single-sided tape, and the single-sided tape is composed of a conductive substrate layer, an adhesive layer and a release film layer stacked in sequence;

[0064] The conductive substrate layer is an electrolytic copper foil with a thickness of 0.018 mm;

[0065] The adhesive layer is made of a bio-based conductive adhesive and has a thickness of 0.012 mm;

[0066] The release film layer is a PET release film with a thickness of 0.05 mm.

[0067] The preparation method of the single-sided adhesive tape comprises the following steps:

[0068] 100 parts by weight of bio-based adhesive (bio-based acrylic adhesive, SP002794), 10 parts by weight of tackifier (rosin resin), 8 parts by weight of conductive filler (branched nickel powder, D 50 8 μm), 1.2 parts by weight of isocyanate silane (XPHJ-G01C), 0.01 parts by weight of epoxy silane (XPHJ-G02C) and 80 parts by weight of ethyl acetate were mixed to form a glue solution, which was coated on one side of the release film layer and dried in an oven at 150°C. The inlet and outlet air volume of the oven was 4500m 3 / h, the drying speed is 10m / min to form an adhesive layer, which is laminated with the conductive substrate layer and placed at room temperature (25°C) for 3 days for aging to obtain the single-sided tape.

[0069] Example 3

[0070] This embodiment provides a bio-based conductive tape and a preparation method thereof, wherein the bio-based conductive tape is a single-sided tape, and the single-sided tape is composed of a conductive substrate layer, an adhesive layer and a release film layer stacked in sequence;

[0071] The conductive substrate layer is an electrolytic copper foil with a thickness of 0.018 mm;

[0072] The adhesive layer is made of a bio-based conductive adhesive and has a thickness of 0.012 mm;

[0073] The release film layer is a PET release film with a thickness of 0.05 mm.

[0074] The preparation method of the single-sided adhesive tape comprises the following steps:

[0075] 100 parts by weight of bio-based adhesive (bio-based acrylic adhesive, SP002794), 15 parts by weight of tackifier (rosin resin), 10 parts by weight of conductive filler (branched nickel powder, D 50 The particle size is 10 μm), 1.2 parts by weight of isocyanate silane (XPHJ-G01C), 0.01 parts by weight of epoxy silane (XPHJ-G02C) and 80 parts by weight of ethyl acetate are mixed to form a glue solution, which is coated on one side of the release film layer and dried in an oven at 80°C. The inlet and outlet air volume of the oven is 4500m 3 / h, the drying speed is 3m / min to form an adhesive layer, which is laminated with the conductive substrate layer and placed at room temperature (25°C) for 7 days for aging to obtain the single-sided tape.

[0076] Example 4

[0077] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from Embodiment 1 only in that the weight portion of isocyanate silane is adjusted to 0.9 parts, and other conditions are the same as Embodiment 1.

[0078] Example 5

[0079] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from Embodiment 1 only in that the weight portion of isocyanate silane is adjusted to 0.5 parts, and other conditions are the same as Embodiment 1.

[0080] Example 6

[0081] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from the embodiment 1 in that the weight portion of the tackifier (rosin resin) is adjusted to 40 parts, and the conductive filler (branched nickel powder, D 50 The weight portion of the particle size is 10 μm) is adjusted to 15 parts, and the other conditions are the same as those in Example 1.

[0082] Example 7

[0083] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from the embodiment 1 only in that the conductive filler (branched nickel powder, D 50 The weight portion of the particle size is 10 μm) is adjusted to 30 parts, and the other conditions are the same as those in Example 1.

[0084] Example 8

[0085] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from the embodiment 1 only in that the conductive filler (branched nickel powder, D 50 The weight portion of the particle size is 10 μm) is adjusted to 4 parts, and the other conditions are the same as those in Example 1.

[0086] Example 9

[0087] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from the embodiment 1 only in that the conductive filler (branched nickel powder, D 50 The particle size is 10 μm) and the conductive filler (branched nickel powder, D 50 The particle size is 20 μm), and other conditions are the same as those in Example 1.

[0088] Example 10

[0089] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from the embodiment 1 only in that the conductive filler (branched nickel powder, D 50 The particle size is 10 μm) and the conductive filler (branched nickel powder, D 50 The particle size is 30 μm), and other conditions are the same as those in Example 1.

[0090] Embodiment 11

[0091] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from the embodiment 1 only in that the conductive filler (branched nickel powder, D 50 The particle size is 10 μm) and replaced with the conductive filler of the same mass (spherical nickel powder, D 50 The particle size is 10 μm), and other conditions are the same as those in Example 1.

[0092] Example 12

[0093] This embodiment provides a bio-based conductive tape and a preparation method thereof, which is different from Embodiment 1 only in that the rosin resin is replaced with a terpene resin of the same mass, and other conditions are the same as those of Embodiment 1.

[0094] Example 13

[0095] This embodiment provides a bio-based conductive tape and a preparation method thereof, which differs from Embodiment 1 only in that epoxy silane is not added, the weight fraction of isocyanate silane (XPHJ-G01C) is adjusted to 1.21 parts, and other conditions are the same as those in Embodiment 1.

[0096] Embodiment 14

[0097] This embodiment provides a bio-based conductive tape and a preparation method thereof, which differs from Embodiment 1 only in that no isocyanate silane is added, the weight fraction of epoxy silane (XPHJ-G02C) is adjusted to 1.21 parts, and other conditions are the same as those in Embodiment 1.

[0098] Comparative Example 1

[0099] This comparative example provides a conductive tape and a preparation method thereof, which is different from Example 1 only in that the bio-based acrylic adhesive (SP002794) is replaced with an acrylic pressure-sensitive adhesive (XPHGS04) of the same quality, and other conditions are the same as those in Example 1.

[0100] The glue solutions provided in the above-mentioned Examples 1-14 and Comparative Example 1 were subjected to the following tests.

[0101] Viscosity of the adhesive: Place the container containing the adhesive in a 25°C constant temperature bath to balance the temperature of the adhesive with the test temperature, and test the viscosity of the adhesive at 25°C. The rotational viscometer method is to measure the viscosity of the adhesive using a rotational viscometer.

[0102] The conductive tapes provided in the above Examples 1-14 and Comparative Example 1 were tested as follows.

[0103] 1inch 2 Resistance: Cut the sample to be tested into a sample with a width of 25.4mm×25.4mm and attach it to the gold-plated resistor fixture (contact area is 25.4×25.4mm). Press it with a 1000g weight for 1 minute and then test the resistance of the sample;

[0104] Peel force: Tested in accordance with the method provided in GB / T 2792-2014; the sample to be tested was cut into a sample with a size of 25.4×300mm. The specific test steps include: at room temperature (25°C), the cut sample was attached to the surface of the SUS304 mirror panel, rolled back and forth 3 times with a 2kg roller, and then left to stand for 20 minutes before testing the 180° peel force test;

[0105] Bio-based content of adhesive layer: the mass percentage of bio-based materials in bio-based adhesive and tackifier in bio-based conductive adhesive.

[0106] The test results are shown in Table 1 below.

[0107] Table 1

[0108]

[0109] From the contents of Table 1, it can be seen that the 1-inch bio-based conductive tape provided in Examples 1-14 2 The average resistance is less than 0.07Ω, the peel force is greater than 800gf, and it has excellent conductive and adhesive properties.

[0110] Compared with Example 1, the bio-based conductive tapes prepared in Examples 4 and 5 have higher peeling force and better adhesion. It can be seen that the weight proportion of the cross-linking agent is preferably 0.01 to 1 part, and the prepared bio-based conductive tape has better peeling force performance.

[0111] Compared with Example 1, if the weight fraction of the conductive filler is too large (Example 7), the peeling force of the prepared bio-based conductive tape is relatively low. If the weight fraction of the conductive filler is too small (Example 8), the resistance of the prepared bio-based conductive tape is relatively high. It can be seen that the weight fraction of the conductive filler is preferably 5 to 15 parts, and the prepared bio-based conductive tape has better performance.

[0112] Compared with Example 1, if the D 50 When the particle size is too large (Example 10), the peeling force of the prepared bio-based conductive tape is reduced, and the surface of the conductive substrate layer is uneven.

[0113] Compared with Example 1, if the branched chain nickel powder is replaced with spherical nickel powder of the same mass (Example 11), the obtained bio-based conductive tape has a large resistance and poor conductivity. It can be seen that the branched chain nickel powder is a conductive filler, and the prepared bio-based conductive tape has better performance.

[0114] Compared with Example 1, if the rosin resin is replaced with the terpene resin of the same mass (Example 12), the performance of the obtained bio-based conductive tape is slightly reduced.

[0115] Compared with Example 1, if epoxy silane is not added (Example 13), the resistance of the obtained bio-based conductive tape is reduced; if isocyanate silane is not added (Example 14), the peeling force of the obtained bio-based conductive tape is reduced. It can be seen that the performance of the bio-based conductive tape prepared by compounding epoxy silane and isocyanate silane as a cross-linking agent is better.

[0116] Compared with Example 1, if the bio-based acrylic adhesive is replaced with an acrylic pressure-sensitive adhesive of the same mass (Comparative Example 1), the bio-based substance content of the adhesive layer is low, the resistance is increased, and the peel force is decreased. It can be seen that the bio-based acrylic adhesive prepared by the combination of the bio-based adhesive, the tackifier, the conductive filler and the cross-linking agent in the present invention has better performance.

[0117] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A bio-based conductive adhesive, characterized in that: The raw materials for preparing the bio-based conductive adhesive include the following components in parts by weight: 100 parts of bio-based adhesive, 1 to 80 parts of tackifier, 3 to 30 parts of conductive filler and 0.01 to 5 parts of cross-linking agent.

2. The bio-based conductive adhesive according to claim 1, characterized in that: The bio-based adhesive includes a bio-based acrylic adhesive; Preferably, the tackifier comprises a bio-based tackifying resin; Preferably, the bio-based tackifying resin comprises any one or a combination of at least two of rosin resin, modified rosin resin, petroleum resin, terpene resin, terpene phenolic resin or phenolic resin; Preferably, the weight proportion of the tackifier in the raw materials for preparing the bio-based conductive adhesive is 1 to 40 parts.

3. The bio-based conductive adhesive according to claim 1 or 2, characterized in that: The softening point of the tackifier is -40 to 150°C, more preferably 0 to 120°C.

4. The bio-based conductive adhesive according to any one of claims 1 to 3, characterized in that: The conductive filler includes metal conductive particles; Preferably, the metal conductive particles include any one of gold powder, copper powder, silver powder, nickel powder, aluminum powder, nickel powder or nickel-coated graphite, or a combination of at least two thereof, and more preferably nickel powder; Preferably, the weight proportion of the conductive filler in the raw materials for preparing the bio-based conductive adhesive is 5 to 15 parts.

5. The bio-based conductive adhesive according to claim 4, characterized in that: The nickel powder includes any one of branched chain nickel powder, flaky nickel powder, spherical nickel powder, porous micro-spherical nickel powder or long chain nickel powder, or a combination of at least two thereof, and branched chain nickel powder is more preferred.

6. The bio-based conductive adhesive according to claim 5, characterized in that: The D 50 Particle size is 5-40 μm; Preferably, the crosslinking agent comprises isocyanate silane and / or epoxy silane, more preferably isocyanate silane and epoxy silane; Preferably, the weight proportion of the crosslinking agent in the raw materials for preparing the bio-based conductive adhesive is 0.01 to 1 part.

7. A method for preparing a bio-based conductive adhesive according to any one of claims 1 to 6, characterized in that: The preparation method comprises mixing a bio-based adhesive, a tackifier, a conductive filler, a cross-linking agent and a solvent, and drying the mixture to obtain the bio-based conductive adhesive.

8. The preparation method according to claim 7, characterized in that: The solvent includes ethyl acetate; Preferably, the drying temperature is 80-160°C; Preferably, the drying speed is 3 to 10 m / min; Preferably, the drying further includes a aging step; Preferably, the aging temperature is 20-30° C. and the time is 3-7 days.

9. A bio-based conductive tape, characterized in that: The bio-based conductive tape includes a tape without a substrate or a tape containing a substrate; The substrate-free adhesive tape comprises a first release film layer, an adhesive layer, and a second release film layer stacked in sequence, wherein the adhesive layer is made of the bio-based conductive adhesive according to any one of claims 1 to 6; The substrate-containing adhesive tape includes a single-sided adhesive tape or a double-sided adhesive tape; The single-sided tape is composed of a release film layer, an adhesive layer and a conductive substrate layer stacked in sequence, and the adhesive layer is made of the bio-based conductive adhesive according to any one of claims 1 to 6; The double-sided tape consists of a first release film layer, a first adhesive layer, a conductive substrate layer, a second adhesive layer and a second release film layer stacked in sequence, and the first adhesive layer and the second adhesive layer are each independently made of the bio-based conductive adhesive as described in any one of claims 1 to 6.

10. The bio-based conductive tape according to claim 9, characterized in that: The first release film layer in the substrate-free tape, the second release film layer in the substrate-free tape, the release film layer in the single-sided tape, the first release film layer in the double-sided tape and the second release film layer in the double-sided tape each independently comprise a plain release film; Preferably, the conductive substrate layers in the single-sided tape and the double-sided tape each independently include any one of copper foil, aluminum foil or conductive cloth, more preferably copper foil; Preferably, the copper foil is an electrolytic copper foil; Preferably, the copper foil has a thickness of 0.002-3.0 mm.

Citation Information

Patent Citations

  • Pressure-sensitive conductive adhesive and preparation method thereof

    CN111500215A